The Benefits of Implementing Corporate Social Responsibility in Mipymes in Medellín - Javier Alonso Villa Yepes; Orlando Carmelo Castellanos Polo (MultiTech Publisher, 2023)
The purpose of this essay is to propose which would be the benefits that MSMEs in the city of Medellin would have with the implementation of Corporate Social Responsibility practices, both in the financial field, brand recognition in the market and positioning in the city, for this it is relevant to frame several relevant concepts on the subject in question, such as the historical review of Corporate Social Responsibility, this review will establish some conceptual definitions of academics of Corporate Social Responsibility. Then a brief description will be made on the subject of MSMEs in Colombia and specifically in Medellin.